2004
DOI: 10.1002/hlca.200490275
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cyclohexapeptides Containing Pro and Aib Residues

Abstract: Cyclization reactions on hexapeptides containing several alpha-aminoisobutyric acid (= 2-amino-2-methylpropanoic acid; Aib) residues and the turn-promoting glycine (Gly) and proline (Pro) residues were investigated. Eight linear hexapeptides were synthesized, and their cyclization was attempted with various coupling reagents. The macrolactamization step proved to be difficult since only three hexapeptides could be cyclized. Two of these latter peptides were the linear precursors of the same cyclic hexapeptide,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…With the exception of epoxy peptide 29 , which was subjected to macrolactonization reaction conditions, following Yamaguchi methodology, the other precursors ( 34 , 41 , and 48 ) were exposed, under high dilution conditions, to a variety of coupling reagents, including diethyl cyanophosphonate (DEPC), diphenyl phosphoryl azide (DPPA), O- (7-azabenzotriazol-1-yl)- N , N , N ‘ , N ‘ -tetramethyluronium hexafluorophosphate/1-hydroxybenzotriazole (HATU/HOBt), O- (benzotriazol-1-yl)- N , N , N ‘ , N ‘ -tetramethyluronium hexafluorophosphate/HOBt (HBTU/HOBt), EDCI/HOBt, and pentafluorophenol/EDCI (PFP/EDCI), in different solvents (DCM, THF, DMF, MeCN). The results from these studies revealed that, whereas the macrolactonization did not work at all for compound 29 , resulting in a complex mixture of decomposition products, the macrolactamizations provided more positive results, especially with the epoxy peptide 34 , which afforded the best yields for the desired macrocycle 8 when it was treated with DPPA or DEPC as coupling reagents and DMF as solvent. The epoxy peptide that was obtained represents an interesting compound for the preparation of the 2,3-epoxy analogue of stevastelin B, as well as representing the direct precursor for the natural compound.…”
Section: Resultsmentioning
confidence: 99%
“…With the exception of epoxy peptide 29 , which was subjected to macrolactonization reaction conditions, following Yamaguchi methodology, the other precursors ( 34 , 41 , and 48 ) were exposed, under high dilution conditions, to a variety of coupling reagents, including diethyl cyanophosphonate (DEPC), diphenyl phosphoryl azide (DPPA), O- (7-azabenzotriazol-1-yl)- N , N , N ‘ , N ‘ -tetramethyluronium hexafluorophosphate/1-hydroxybenzotriazole (HATU/HOBt), O- (benzotriazol-1-yl)- N , N , N ‘ , N ‘ -tetramethyluronium hexafluorophosphate/HOBt (HBTU/HOBt), EDCI/HOBt, and pentafluorophenol/EDCI (PFP/EDCI), in different solvents (DCM, THF, DMF, MeCN). The results from these studies revealed that, whereas the macrolactonization did not work at all for compound 29 , resulting in a complex mixture of decomposition products, the macrolactamizations provided more positive results, especially with the epoxy peptide 34 , which afforded the best yields for the desired macrocycle 8 when it was treated with DPPA or DEPC as coupling reagents and DMF as solvent. The epoxy peptide that was obtained represents an interesting compound for the preparation of the 2,3-epoxy analogue of stevastelin B, as well as representing the direct precursor for the natural compound.…”
Section: Resultsmentioning
confidence: 99%
“…One of the molecules forms a β-turn with a Aib 4 →Gly 1 hydrogen bond, whereas the other molecule is characterized by a γturn (NH(Aib 4 )→CO(Pro 3 ) hydrogen bond) and an α-turn (NH(Phe 5 )-CO(Gly 1 ) hydrogen bond). In both molecules, Aib4 shows φ,ψ values that belong to the nonhelical conformational space.As a part of our investigation of the synthesis of cyclic hexapeptides containingAib residues,6,22 we have been interested in the conformations of these cyclic molecules in order to estimate if the incorporation of several Aib residues into cyclic hexapeptide structures stabilizes certain types of turns. Previously, we have investigated the cyclization and conformation of hexapeptides containing two or three Aib residues, and two Gly residues in positions 1 and 4 of the peptide backbone 6.…”
mentioning
confidence: 99%
“…33 Peptides 13 and 14 were evaluated to determine whether more cyclization-prone substrates could be efficiently functionalized (Table 4). The proclivity of these peptides towards macrocyclization was validated by control reactions with MeOH/Hünig’s base and Hünig’s base alone (entry 2,3,5,6).…”
mentioning
confidence: 99%